The use of vascularised muscle flaps for treatment or prevention of wound complications following arterial surgery in the groin. Issue 6 (3rd August 2020) - Price, Annie; Contractor, Ummul; White, Richard; Williams, Ian
Abstract: Wound complications following arterial surgery in the groin are relatively common and can result in significant morbidity and mortality. Vascularised muscle flaps (VMF) may be used as an adjunct to aid healing, either to manage complications or prophylactically. This series describes 46 patients who received sartorius or gracilis muscle flaps, of which 70% were performed as a salvage procedure to treat complications ranging from wound breakdown to vascular graft infection. The remaining 30% were performed at the time of the arterial surgery in patients with risk factors such as re‐do surgery or immunosuppression. The peri‐operative mortality rate was 9% and the major amputation rate was 26%, reflecting the complexity of patients that require intervention. Overall, 85% achieved successful healing in the groin without the need for further treatment following VMF. Only one case of flap necrosis occurred. Wound healing complications occurred more commonly after sartorius muscle flaps. The gracilis muscle offers a bulkier mass and greater mobility and so may be preferable, particularly for larger groin defects. This series has shown that VMF offer a safe and reliable option for selected cases to achieve wound healing in the groin in patients with often significant co‐morbidities.